2016
DOI: 10.1523/jneurosci.2526-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Loss ofPtf1aLeads to a Widespread Cell-Fate Misspecification in the Brainstem, Affecting the Development of Somatosensory and Viscerosensory Nuclei

Abstract: The brainstem contains diverse neuronal populations that regulate a wide range of processes vital to the organism. Proper cell-fate specification decisions are critical to achieve neuronal diversity in the CNS, but the mechanisms regulating cell-fate specification in the developing brainstem are poorly understood. Previously, it has been shown that basic helix-loop-helix transcription factor Ptf1a is required for the differentiation and survival of neurons of the inferior olivary and cochlear brainstem nuclei,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…The basic pattern of bHLH genes is supplemented by addition of other bHLH and homeobox factors (Hernandez-Miranda et al, 2016) and shows local, rhombomere-specific variation in the hindbrain. Most importantly, bHLH genes such as Ptf1a are both highly conserved in their expression (Sugahara et al, 2016) but also elicit a local rearrangement of nuclear development when mutated (Iskusnykh et al, 2016). How the GRNs of spinal cord cellular population are both systematically and rhombomere-specifically influenced to give rise to the four above mentioned nuclei dedicated to processing the information from the ear in vestibular and cochlear nuclei as well as the mechanosensory and electrosensory lateral line nuclei remains to be determined in the light of an apparently rather stable Hox code (Krumlauf, 2016; Murakami et al, 2004; Parker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic pattern of bHLH genes is supplemented by addition of other bHLH and homeobox factors (Hernandez-Miranda et al, 2016) and shows local, rhombomere-specific variation in the hindbrain. Most importantly, bHLH genes such as Ptf1a are both highly conserved in their expression (Sugahara et al, 2016) but also elicit a local rearrangement of nuclear development when mutated (Iskusnykh et al, 2016). How the GRNs of spinal cord cellular population are both systematically and rhombomere-specifically influenced to give rise to the four above mentioned nuclei dedicated to processing the information from the ear in vestibular and cochlear nuclei as well as the mechanosensory and electrosensory lateral line nuclei remains to be determined in the light of an apparently rather stable Hox code (Krumlauf, 2016; Murakami et al, 2004; Parker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chief among those is Ptf1a, a bHLH transcription factor that is essential for cerebellar (Pascual et al, 2007) (Millen et al, 2014) and dorsal cochlear nucleus development (Fujiyama et al, 2009) but other bHLH genes play a role as well (Cai et al, 2016). In addition, to be relevant for the formation of nuclei or brain areas, Ptf1a also plays an essential role in cell fate determination within a given nucleus defining excitatory and inhibitory neurons (Iskusnykh et al, 2016) Beyond formation of entire nuclei, several genes are now emerging that interact to define different cell types in different brainstem nuclei important for their normal function (Nothwang, 2016). Above we outlined how multiplication of existing cell fate determining bHLH genes provides the molecular start of distinct cell fate evolution (Arendt et al, 2016; Fritzsch et al, 2000) for neurosensory evolution of the ear.…”
Section: Introductionmentioning
confidence: 99%
“…The first of these inventions is the set of epidermal placodes that are present only in craniate chordates [Northcutt and Gans 1983]. In addition to placodes associated with gustatory [Iskusnykh et al 2016; Qian et al 2001], paratympanic and spiracular organs [O’Neill et al 2012], regionally localized placodes give rise to lateral line, electroreceptive and vestibular/auditory neurons, which project to specific nuclear areas in the dorsolateral part of the hindbrain [Dabdoub et al 2016; Straka et al 2014]. The evolutionary origin of these placodes is not clear.…”
Section: Placodes and Dedicated Hindbrain Nuclei: Pivotal Vertebratementioning
confidence: 99%
“…For example, each rhombomere is characterized by a unique code of Hox gene expression [Krumlauf 2016], and each longitudinal column expresses a specific set of dorsoventrally disposed TFs. Some of the longitudinal columns in the hindbrain are continuous with those in the spinal cord, including columns in the alar plate that express the TFs Atoh1 [Bermingham et al 2001], Neurog1/2 [Fritzsch et al 2006], Ascl1 [Qian et al 2001] and Ptf1a [Bermingham et al 2001; Fritzsch et al 2006; Iskusnykh et al 2016; Ma et al 1997]. Others, however, are not [Nieuwenhuys and Puelles 2015].…”
Section: Placodes and Dedicated Hindbrain Nuclei: Pivotal Vertebratementioning
confidence: 99%
“…Previous studies have identified basic helix-loop-helix (bHLH) transcription factors as crucial regulators of neuronal subtype specification in the dorsal spinal cord where somatosensory information is processed (Glasgow et al, 2005; Gowan et al, 2001; Helms et al, 2005; Mizuguchi et al, 2006; Muller et al, 2005; Ross et al, 2010; Wildner et al, 2013). PTF1A is one such factor, initially identified as critical for pancreas development that is also required for specification of inhibitory neurons in various regions of the developing CNS including the spinal cord, brainstem, cerebellum, and retina (Dullin et al, 2007; Fujitani et al, 2006; Glasgow et al, 2005; Hoshino et al, 2005; Iskusnykh et al, 2016; Kawaguchi et al, 2002; Millen et al, 2014; Nakhai et al, 2007; Pascual et al, 2007; Yamada et al, 2007). In the dorsal spinal cord, PTF1A is induced in a population of progenitor cells that will give rise to inhibitory neurons when PTF1A is present, but in its absence the progenitors differentiate into excitatory neurons (Glasgow et al, 2005).…”
Section: Introductionmentioning
confidence: 99%